The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1872-034x.2008.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Common null variant, Arg192Stop, in a G‐protein coupled receptor, olfactory receptor 1B1, associated with decreased serum cholinesterase activity

Abstract: These results suggested that the null-allele of OR1B1 might affect metabolism of serum cholinesterase in carriers of this nSNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The design and methods of these studies have been reported elsewhere (12)(13)(14). Briefly, the study was designed to evaluate the role of lifestyle, diet, and genetic factors in the subsequent development of many common diseases.…”
Section: Study Populationmentioning
confidence: 99%
“…The design and methods of these studies have been reported elsewhere (12)(13)(14). Briefly, the study was designed to evaluate the role of lifestyle, diet, and genetic factors in the subsequent development of many common diseases.…”
Section: Study Populationmentioning
confidence: 99%
“…The OR1B1 SNP leads to truncation of the 7-transmembrane receptor domain present in OR1B1 (Figure  4C). This truncated variant of OR1B1 protein has been observed in a recent study [39] and is thought to affect metabolism of serum cholinesterase [40]. Overall, our assessment of the effect of the nsSNPs using SIFT [41] indicates that 1,460 are likely damaging (Additional file 1: Table S3).…”
Section: Resultsmentioning
confidence: 71%
“…SIX homeobox 1 ( SIX1 ) gene was reported to be involved in embryogenesis, cellular specification, and postnatal gonad development in mammals. OR2BI is a G-protein-coupled receptor and involved in liver cell metabolism ( 49 ). Orthopedia homeobox (OTP ) was used as a potential marker for lung carcinoids in humans ( 50 ).…”
Section: Discussionmentioning
confidence: 99%